2015
DOI: 10.4329/wjr.v7.i4.70
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of magnetic resonance cholangiography compared to operative endoscopy in detecting biliary stones, a single center experience and review of literature

Abstract: AIM:To compare diagnostic sensitivity, specificity and accuracy of magnetic resonance cholangiopancreatography (MRCP) without contrast medium and endoscopic ultrasound (EUS)/endoscopic retrograde cholangiopancreatography (ERCP) for biliary calculi. METHODS:From January 2012 to December 2013, two-hundred-sixty-three patients underwent MRCP at our institution, all MRCP procedure were performed with the same machinery. In two-hundred MRCP was done for pure hepatobiliary symptoms and these patients are the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 24 publications
2
22
2
5
Order By: Relevance
“…Some studies found the specificity of MRCP to be between 40% and 100%. In this perspective, in our study, the sensitivity result seems to be in the medium sensitivity group [1,4]. In a comparison of the specificity value with other series, we found a lower value because the first observer reported suspected stone in the bile ducts of two patients and the second observer in three patients.…”
Section: Discussioncontrasting
confidence: 42%
“…Some studies found the specificity of MRCP to be between 40% and 100%. In this perspective, in our study, the sensitivity result seems to be in the medium sensitivity group [1,4]. In a comparison of the specificity value with other series, we found a lower value because the first observer reported suspected stone in the bile ducts of two patients and the second observer in three patients.…”
Section: Discussioncontrasting
confidence: 42%
“…Radial sections, which are obtained perpendicular to anatomical surfaces in a fraction of the time, provide true cross sections that differ from those provided by conventional planes [10]. Radial imaging is not a new technique; it is utilized in clinical settings (e.g., MR of cholangiopancreatography) [11]. However, for musculoskeletal (MSK) imaging, radial imaging was first introduced by Munk, Holt, Helms, & Genant [12] and Quinn, Brown, & Szumowski [13], who used this technique to examine the shoulder and knee, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Most researchers have reported that these new MRCP sequences are even better than ERCP because they accurately diagnoses pancreatobiliary diseases [24,3,9].MRCP is a less costly, non-invasive, and sensitive technique for evaluating the biliary and pancreatic ductal systems.…”
Section: Issn: 2320-5407mentioning
confidence: 99%